Relationship between respiratory quotient, nitrification, and nitrous oxide emissions in a forced aerated composting process. (August 2015) - Tsutsui, Hirofumi; Fujiwara, Taku; Inoue, Daisuke; Ito, Ryusei; Matsukawa, Kazutsugu; Funamizu, Naoyuki
Highlights: RQ can be an indicator of N2 O emission in forced aerated composting process. Emission of N2 O with nitrification was observed with RQ decrease. Mass balances demonstrated the RQ decrease was caused by nitrification. Conversion ratio of oxidized ammonia and total N to N2 O were ∼2.7%. Abstract: We assessed the relationship between respiratory quotient (RQ) and nitrification and nitrous oxide (N2 O) emission in forced aerated composting using lab-scale reactors. Relatively high RQ values from degradation of readily degradable organics initially occurred. RQ then stabilized at slightly lower values, then decreased. Continuous emission of N2 O was observed during the RQ decrease. Correlation between nitrification and N2 O emission shows that the latter was triggered by nitrification. Mass balances demonstrated that the O2 consumption of nitrification (∼24.8 mmol) was slightly higher than that of CO2 emission (∼20.0 mmol), indicating that the RQ decrease was caused by the occurrence of nitrification. Results indicate that RQ is a useful index, which not only reflects the bioavailability of organics but also predicts the occurrence of nitrification and N2 O emission in forced aerated composting.